Hydrophilic structural adhesive applied to hygienic products

Through specific formulas and preparation processes, a hydrophilic structural glue for sanitary products is prepared, which solves the problem of improving hydrophilicity in the prior art that affects other performances, and achieves a combination of efficient liquid absorption and stable performance.

CN119505770APending Publication Date: 2025-02-25XIAMEN QIXING NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411751274.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

While improving the hydrophilicity of adhesives and materials on the surface, the prior art often affects their other properties, such as bonding strength, stability, flexibility and breathability, limiting their application range and effects.

Method used

Through specific formulation and preparation processes, a hydrophilic structural glue used for sanitary products is prepared using components such as plasticizers, polymer thermoplastic elastomers, surfactants, tackifying resins and antioxidants.

Benefits of technology

While improving the hydrophilicity of adhesives and materials, it maintains or optimizes its other properties, such as bonding strength, stability, flexibility and breathability, thus expanding its application range and improving the liquid absorption capacity of infant and toddler diapers and feminine hygiene products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505770A_ABST
    Figure CN119505770A_ABST
Patent Text Reader

Abstract

The invention provides a hydrophilic structural adhesive applied to hygienic products. The hydrophilic structural adhesive is prepared from a plasticizer, a polymer thermoplastic elastomer, a surfactant, tackifying resin and an antioxidant. By optimizing the proportion of the components and a specific preparation process, the hydrophilic structural adhesive disclosed by the invention not only improves the hydrophilicity and liquid absorption capacity of a material, but also can keep good bonding strength, stability, softness and air permeability of the material, and is suitable for the fields of infant diapers, female hygienic products and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adhesives, in particular to a hydrophilic structural adhesive used for sanitary products. Background Art

[0002] In the field of adhesive preparation technology, hydrophilic structural adhesive is an important material, which is widely used in the manufacture of sanitary products, such as baby diapers and feminine hygiene products. The main function of this structural adhesive is to improve the liquid absorption capacity of the product, so that the product can quickly absorb and lock the liquid, keeping it dry and comfortable. In addition, material surface treatment technology also plays a key role in this process, which can change the surface properties of the material, improve its hydrophilicity, and thus improve the liquid absorption capacity of the product.

[0003] In the prior art, although there are some methods to improve the hydrophilicity of the adhesive by changing the formulation or preparation process of the adhesive, such as changing the reaction conditions, adjusting the ratio of raw materials, etc., improving the hydrophilicity often affects other properties, such as bonding strength and stability, which limits the application scope and effect of the prior art.

[0004] Therefore, how to improve the hydrophilicity of adhesives and material surfaces without affecting their other properties is an important challenge facing current technology.

[0005] In view of this, the inventor specially designed a hydrophilic structural adhesive for use in sanitary products, and this case was thus generated. Summary of the invention

[0006] In order to solve the following technical problems: 1) how to improve the hydrophilicity of the adhesive without affecting its bonding strength and stability; 2) how to improve the hydrophilicity of the material surface without affecting its other properties such as softness and breathability; 3) how to achieve simultaneous improvement of the hydrophilicity of the adhesive and the material surface to improve the liquid absorption capacity of infant diapers and feminine hygiene products, one of the technical solutions of the present invention is as follows: A hydrophilic structural adhesive for use in sanitary products is prepared from the following components in parts by weight: Plasticizer, 5-35 parts; Polymer thermoplastic elastomer (hereinafter referred to as polymer SIS), 10-35 parts; Surfactant, 1-15 parts; Tackifying resin, 36-65 parts; Antioxidant, 0.1-2 parts.

[0007] Preferably, the polymer SIS is selected from a thermoplastic elastomer 1 having a styrene content of 15-30% and a diblock content of less than 1% (hereinafter referred to as SIS1) and a thermoplastic elastomer 2 having a styrene content of 15-30% and a diblock content of 30-60% (hereinafter referred to as SIS2).

[0008] Preferably, the mass ratio of SIS1 to SIS2 is 1:(1.5-3).

[0009] Preferably, the SIS1 is selected from the thermoplastic elastomer 1100 or the thermoplastic elastomer 1300 or the thermoplastic elastomer 1209 , and the SIS2 is selected from the thermoplastic elastomer 1120 or the thermoplastic elastomer 1250 or the thermoplastic elastomer 1126 .

[0010] Preferably, the tackifying resin is selected from one of hydrogenated C5 petroleum resin, hydrogenated C5 / C9 copolymer resin, hydrogenated terpene resin, hydrogenated DCPD resin and hydrogenated C9 petroleum resin.

[0011] Preferably, the plasticizer is selected from cycloalkane oil and white oil.

[0012] Preferably, the antioxidant is selected from one of the antioxidant model 1010 produced by Foshan Yuansheng Chemical Co., Ltd. and the antioxidant model 215 produced by Foshan Yuansheng Chemical Co., Ltd.

[0013] Preferably, the surfactant is one or more of polyoxyethylene (20) sorbitan monolaurate, polyoxyethylene sorbitan monostearate, and fatty alcohol polyoxyethylene ether.

[0014] The second technical solution of the present invention is as follows: A method for preparing a hydrophilic structural adhesive comprises the following steps: S1. Before adding materials, make sure that the bottom valve of the reactor is closed, open the lid of the reactor, turn on the stirring paddle switch, add plasticizer, polymer SIS and antioxidant in sequence, and then turn on the reactor jacket for heating; S2, raising the temperature of the reactor in S1 to 160-170°C, stirring for 2-3 hours until the polymer thermoplastic elastomer is completely melted; S3, evenly adding tackifying resin into the reaction kettle in S2, and continuing to stir until the tackifying resin is completely melted and fully mixed; S4, adding surfactant evenly into the reaction kettle in S3, and continuing to stir until the surfactant is fully mixed; S5, after the stirring and mixing in S4 is completed, the molten material in the reactor is filtered through a filter screen in the filter to remove impurities; S6, passing the molten material filtered in S5 through a film packaging machine, a cooling system, and a drying system in sequence to cool and solidify it, and finally packing it into boxes.

[0015] The third technical solution of the present invention is as follows: The invention discloses an application of a hydrophilic structural adhesive for the manufacture of diapers and sanitary products.

[0016] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention improves the hydrophilicity of the adhesive and the surface of the material through a special preparation process and formula, so that the product can quickly absorb and lock the liquid, keep it dry and comfortable, and greatly improve the use effect of the product.

[0017] 2. Compared with the prior art, the present invention improves the hydrophilicity of the adhesive and the material surface without affecting other properties, such as bonding strength, stability, etc. In addition, the present invention improves the hydrophilicity of the material surface without changing other properties of the material, such as softness, air permeability, etc., thereby expanding its application range.

[0018] 3. The raw materials of the present invention are all environmentally friendly and safe materials, non-toxic and harmless, friendly to the environment, and meet the requirements of modern society for environmental protection.

[0019] 4. The preparation process of the present invention is simple, the raw materials are readily available, the production cost is low, it is conducive to large-scale industrial production, and meets the market demand for high-efficiency, low-cost products.

[0020] 5. The hydrophilic structural adhesive prepared by the present invention is used in the manufacture of diapers and sanitary products to improve the liquid absorption efficiency of diapers and sanitary products and prevent liquid leakage caused by insufficient absorption speed. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The drawings described herein are used to provide further understanding of the present invention and constitute a part of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0022] in: Figure 1 It is a flowchart of the preparation method of the present invention; Figure 2 It is a schematic diagram of the test method of slippage in the present invention. DETAILED DESCRIPTION

[0023] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present invention clearer and more understandable, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0024] The raw materials were weighed according to the ratios in the following table, and hot melt adhesives were prepared according to the following preparation method to obtain hot melt adhesives of different embodiments, as shown in the following table:

[0025] Reference Figure 1 , the preparation process is as follows: S1. Before adding materials, make sure that the bottom valve of the reactor is closed, open the lid of the reactor, turn on the stirring paddle switch, add plasticizer, polymer SIS and antioxidant in sequence, and then turn on the reactor jacket for heating; S2, raising the temperature of the reactor in S1 to 160-170°C, stirring for 2-3 hours until the thermoplastic elastomer is completely melted; S3, evenly adding tackifying resin into the reaction kettle in S2, and continuing to stir until the tackifying resin is completely melted and fully mixed; S4, adding surfactant evenly into the reaction kettle in S3, and continuing to stir until the surfactant is fully mixed; S5, after the stirring and mixing in S4 is completed, the molten material in the reactor is filtered through a filter screen in the filter to remove impurities; S6, passing the molten material filtered in S5 through a film packaging machine, a cooling system, and a drying system in sequence to cool and solidify it, and finally packing it into boxes.

[0026] Wherein, if there is no special explanation, the polymer SIS in the table is selected from SIS1300 and SIS1250 with a mass ratio of 1:2; the surfactant is selected from polyoxyethylene (20) sorbitan monolaurate, the plasticizer is selected from cyclohexane oil; the tackifying resin is selected from hydrogenated DCPD petroleum resin with the brand name ER-400 produced by Zhongyi Chemical (Zhangzhou) Co., Ltd.; the antioxidant is selected from the antioxidant with the model number 1010 produced by Foshan Yuansheng Chemical Co., Ltd. In the text, SIS refers to thermoplastic elastomer, followed by a 4-digit number which is its brand name.

[0027] Compared with Example 3, the formula difference of the hot melt adhesive in Comparative Example 1 lies in the different selection ratio of polymer SIS, that is, polymer SIS is selected from SIS1300 and SIS1250 in a mass ratio of 1:1, and the remaining formula amounts are shown in the above table. The preparation process steps and reagents used are the same as those in Example 3.

[0028] Compared with Example 3, the formula difference of the hot melt adhesive in Comparative Example 2 lies in the different selection ratio of polymers, that is, the polymer SIS is selected from SIS1300 and SIS1250 with a mass ratio of 1:3, and the remaining formula amounts are shown in the above table. The preparation process steps and reagents used are the same as those in Example 3.

[0029] Compared with Example 3, the formula difference of the hot melt adhesive in Comparative Example 3 lies in the selection of different polymers, that is, the polymer SIS is selected from SIS1220 with a styrene content of 25% and a diblock content of 25% and SIS1100 with a styrene content of 15% and a diblock content of <1% in a mass ratio of 1:2. The remaining formula amounts are shown in the table above. The preparation process steps and reagents used are the same as those in Example 3.

[0030] Compared with Example 3, the formula of the hot melt adhesive of Comparative Example 4 differs in the selection of polymers, that is, the polymer SIS is selected from SIS1209 with a styrene content of 29% and a diblock content of 0 and SIS1126 with a styrene content of 16% and a diblock content of 50% in a mass ratio of 1:2. The remaining formula amounts are shown in the table above. The preparation process steps and reagents used are the same as those in Example 3.

[0031] Compared with Example 3, the formula difference of the hot melt adhesive in Comparative Example 5 is the lack of surfactant. The remaining formula amounts refer to the above table. The preparation process steps and reagents used are the same as those in Example 3.

[0032] Compared with Example 3, the formula difference of the hot melt adhesive in Comparative Example 6 is that the tackifying resin is Henghe H5-1001, and the remaining formula amounts are referred to the above table. The preparation process steps and reagents used are the same as those in Example 3.

[0033] The physical properties and mechanical properties of the hot melt adhesives of Examples 1-4 and Comparative Examples 1-6 were tested, and the test items and results are shown in the table below.

[0034] 1. Viscosity test method According to GB / T 2784-2013 standard method, Shanghai Jingtian Electronic Instrument Co., Ltd. SNB-RH digital viscometer and No. 27 rotor are used to measure viscosity. The result unit is (CPS). 2. Softening point test method The softening point was tested according to the GB / T 15332 standard method using the SD-0606T automatic softening point tester from the Shanghai Institute of Geoscience Instruments. The result is expressed in (℃).

[0035] 3. Peel strength test method Use a coating machine to spray hot melt adhesive on the water-repellent non-woven fabric, with an adhesive amount of 2g / m2, and then compound it with the PE breathable film, and cut a sample with a width of 25mm and a length of 250mm. Test the 180° peel strength. Place the coated sample in an oven at 60°, age it for 72h, and test the 180° peel strength after aging.

[0036] 4. Test method of slippage Reference Figure 2, use a coating machine to spray hot melt adhesive on the perforated water-repellent non-woven fabric, the amount of adhesive is 2g / m2, and then composite it with the composite core and PE breathable film, cut a 20cm wide and 30cm long sample, first place the tester in a horizontal position, adjust the angle between the upper panel and the lower panel to (30±2)°, and then adjust the lower opening of the funnel so that the projection of its center point is (200±2)mm from the lower edge of the tester inclined panel, and the opening of the lower opening of the funnel faces the operator. Pour an appropriate amount of test solution into the funnel to moisten the funnel, and wash the funnel twice with the test solution and then release it for use.

[0037] Take a sample to be tested and place it flat on the inclined panel of the tester with the surface facing upward. Adjust the height of the funnel so that the lower end of its lower opening is 5mm~10mm away from the surface of the sample. Then place a beaker under the tester to collect the solution that flows down after the sample penetrates.

[0038] Use a measuring cylinder to accurately measure 5mL of the test solution (0.9% saline solution) and pour it into the adjusted standard liquid discharge funnel. Then quickly open the funnel valve to the maximum, allowing the solution to flow freely onto the surface of the sample and flow down the slope into the beaker. After the solution has flowed out, close the funnel valve and wipe the bottom of the funnel to make sure there is no solution. Use a measuring cylinder to measure the solution in the beaker (accurate to 1mL) as the test result. If the test solution flows away from the side of the sample, the sample is invalid and another sample is taken for retesting.

[0039] A2.2 Calculation of slip test results The slippage is expressed as the volume (mL) of the test solution not absorbed by the sample. Seven tests are conducted on each sample. The maximum and minimum values ​​among the seven test results are removed, and the arithmetic mean of the remaining five results is taken as the final test result, accurate to 1 mL.

[0040] 6. The hydrophilicity test method of hydrophilic structural adhesive is as follows: 6.1 Contact angle measurement method: The hydrophilicity test of hydrophilic structural adhesives is usually evaluated by measuring their contact angle. The contact angle is the angle at the intersection of solid, liquid and gas when a liquid is dropped on a solid surface. A smaller contact angle (generally less than 90°) indicates better hydrophilicity, while a larger contact angle indicates hydrophobicity. For hydrophilic structural adhesives, ideal hydrophilicity may require the contact angle to be lower than a certain value, such as 30° to 60°, depending on the application scenario and performance requirements.

[0041] When performing hydrophilicity testing, the following general steps can be followed: 6.2 Operation steps: a. Prepare the sample: Make sure the surface of the structural adhesive sample is clean, flat and free of contamination.

[0042] b. Select standard solution: Purified water is generally used as the test solution because it is the most common hydrophilic test medium.

[0043] c. Titrate the liquid: Using a micropipette or a rubber-tipped dropper, slowly add a drop of water onto the surface of the colloid.

[0044] d. Observe and measure: Use a contact angle meter, which is usually equipped with a camera and analysis software, to drop a drop of pure water or other suitable liquid on the surface of the colloid and calculate the contact angle through image analysis.

[0045] e. Repeated measurements: To improve the reliability of the data, multiple measurements are usually taken at different locations and the average value is taken.

[0046] Test results:

[0047] As shown in the table above, compared with Example 3, the formula differences of Comparative Examples 1-4 are that the types and proportions of polymer SIS are different, where: In comparative example 1, the polymer SIS is selected from SIS1300 and SIS1250 in a mass ratio of 1:1. The hot melt adhesive has a low peel strength, a large decrease in peel strength after aging, a large contact angle, and an increased slippage amount.

[0048] In comparative example 2, the polymer SIS is selected from SIS1300 and SIS1250 in a mass ratio of 1:3. The hot melt adhesive has a low peel strength, a large decrease in peel strength after aging, a large contact angle, and an increased slippage amount.

[0049] In comparative example 3, the polymer SIS is selected from SIS1220 and SIS1100 in a mass ratio of 1:2. The hot melt adhesive has a low peel strength, a large decrease in peel strength after aging, a large contact angle, and an increased slippage amount.

[0050] In comparative example 4, the polymer SIS is selected from SIS1209 and SIS1126 in a mass ratio of 1:2. The hot melt adhesive has a lower peel strength, and the peel strength decreases significantly after aging. The contact angles are the same, and the slippage amounts are similar.

[0051] Compared with Example 3, the formulations of Comparative Examples 5-6 were tested by abandoning the surfactant and changing the type of tackifying resin, wherein: The hot melt adhesive formulation of Comparative Example 5 omits the surfactant based on Example 3. The hot melt adhesive has a high peel strength, but a too large contact angle, and the slippage amount increases nearly three times.

[0052] The formula of the hot melt adhesive in Comparative Example 6 is different from that in Example 3, in which the tackifying resin DCPD hydrogenated petroleum resin ER-400 is changed to C5 hydrogenated petroleum resin H5-1001. After aging, the peel strength of the hot melt adhesive decreases too obviously, the slippage increases, and the contact increases.

[0053] Due to the advanced nature of the technical solution, it can be widely used in application fields such as adhesive preparation, diaper and sanitary product manufacturing, and material surface treatment.

[0054] First, the technical solution can effectively improve the hydrophilicity of the adhesive, thereby improving the liquid absorption capacity of the product, which is of great significance for sanitary products that need to quickly absorb and lock liquids, such as baby diapers and feminine hygiene products.

[0055] Secondly, this technical solution can improve the hydrophilicity of the adhesive without affecting its other properties, such as bonding strength and stability, which will greatly expand its application range in the field of adhesive preparation.

[0056] In particular, the technical solution can also improve the hydrophilicity of the material surface without affecting other properties of the material, such as softness, air permeability, etc., which will have broad application prospects in the field of material surface treatment technology.

[0057] Finally, the hydrophilic structural adhesive prepared in the present application is used in the manufacture of diapers and sanitary products to improve the liquid absorption efficiency of diapers and sanitary products and prevent liquid leakage caused by insufficient absorption speed.

[0058] Therefore, this technical solution has broad market demand and good application prospects.

[0059] The present invention is described above by way of example in conjunction with the accompanying drawings. It is obvious that the specific implementation of the present invention is not limited to the above-mentioned method. As long as various non-substantial improvements are made using the method concept and technical solution of the present invention, or the concept and technical solution of the present invention are directly applied to other occasions without improvement, they are all within the protection scope of the present invention.

Claims

1. A hydrophilic structural adhesive used in sanitary products, characterized in that: It is prepared from the following components in parts by weight: Plasticizer, 5-35 parts; Polymer thermoplastic elastomer, 10-35 parts; Surfactant, 1-15 parts; Tackifying resin, 36-65 parts; Antioxidant, 0.1-2 parts.

2. The hydrophilic structural adhesive for use in sanitary products according to claim 1, characterized in that: The polymer thermoplastic elastomer is selected from a thermoplastic elastomer 1 having a styrene content of 15-30% and a diblock content of less than 1% and a thermoplastic elastomer 2 having a styrene content of 15-30% and a diblock content of 30-60%.

3. The hydrophilic structural adhesive for sanitary products according to claim 2, characterized in that: The mass ratio of the thermoplastic elastomer 1 to the thermoplastic elastomer 2 is 1:(1.5-3).

4. The hydrophilic structural adhesive for use in sanitary products according to claim 2, characterized in that: The first thermoplastic elastomer is selected from the thermoplastic elastomer 1100 , the thermoplastic elastomer 1300 , or the thermoplastic elastomer 1209 , and the second thermoplastic elastomer is selected from the thermoplastic elastomer 1120 , the thermoplastic elastomer 1250 , or the thermoplastic elastomer 1126 .

5. The hydrophilic structural adhesive for sanitary products according to claim 1, characterized in that: The tackifying resin is selected from one of hydrogenated C5 petroleum resin, hydrogenated C5 / C9 copolymer resin, hydrogenated terpene resin, hydrogenated DCPD resin and hydrogenated C9 petroleum resin.

6. The hydrophilic structural adhesive for sanitary products according to claim 1, characterized in that: The plasticizer is selected from naphthenic oil and white oil.

7. The hydrophilic structural adhesive for sanitary products according to claim 1, characterized in that: The antioxidant is selected from one of the antioxidant model 1010 produced by Foshan Yuansheng Chemical Co., Ltd. and the antioxidant model 215 produced by Foshan Yuansheng Chemical Co., Ltd.

8. The hydrophilic structural adhesive for use in sanitary products according to claim 1, characterized in that: The surfactant is one or more of polyoxyethylene (20) sorbitan monolaurate, polyoxyethylene sorbitan monostearate, and fatty alcohol polyoxyethylene ether.

9. A method for preparing a hydrophilic structural adhesive as claimed in claim 1, characterized in that: The steps include: S1. Before adding materials, confirm that the bottom valve of the reactor is closed, open the lid of the reactor, turn on the stirring paddle switch, add plasticizer, polymer thermoplastic elastomer and antioxidant in sequence, and then turn on the reactor jacket for heating; S2, raising the temperature of the reactor in S1 to 160-170°C, stirring for 2-3 hours until the polymer thermoplastic elastomer is completely melted; S3, evenly adding tackifying resin into the reaction kettle in S2, and continuing to stir until the tackifying resin is completely melted and fully mixed; S4, adding surfactant evenly into the reaction kettle in S3, and continuing stirring until the surfactant is fully mixed; S5, after the stirring and mixing in S4 is completed, the molten material in the reactor is filtered through a filter screen in the filter to remove impurities; S6, passing the molten material filtered in S5 through a film packaging machine, a cooling system, and a drying system in sequence to cool and solidify it, and finally packing it into boxes.

10. A use of the hydrophilic structural adhesive as claimed in claim 1, characterized in that: Used in the manufacture of diapers and sanitary products.